2021
DOI: 10.1016/j.cjca.2020.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functioning, Mental Health, and Quality of Life in Different Congenital Heart Defects: Comparative Analysis in 3538 Patients From 15 Countries

Abstract: Background: We compared physical functioning, mental health, and quality of life (QoL) of patients with different subtypes of congenital heart disease (CHD) in a large international sample and investigated the role of functional class in explaining the variance in outcomes across heart defects. Methods: In the cross-sectional Assessment of Patterns of Patient-Reported Outcome in Adults with Congenital Heart Disease-International Study (APPROACH-IS), we enrolled 4028 adult patients with CHD from 15 countries. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
2
27
1
2
Order By: Relevance
“…Unfortunately, the type of TGA and the kind of treatment of the patients are not described in the study, which makes a comparison difficult. 27 Several studies assessing hrQoL in patients with TGA could demonstrate very good results in accordance to this study. Both Culbert et al and Müller et al showed excellent hrQoL for patients with TGA after different types of procedures with better scores than the reference population.…”
Section: Commentsupporting
confidence: 90%
See 2 more Smart Citations
“…Unfortunately, the type of TGA and the kind of treatment of the patients are not described in the study, which makes a comparison difficult. 27 Several studies assessing hrQoL in patients with TGA could demonstrate very good results in accordance to this study. Both Culbert et al and Müller et al showed excellent hrQoL for patients with TGA after different types of procedures with better scores than the reference population.…”
Section: Commentsupporting
confidence: 90%
“…25,26 Moons et al conclude that the hrQoL is more associated with the functional status of the individual than with the severity of the CHD. 25 Indeed, complex CHD showed especially low scores for physical functioning and functional status in different studies, resulting in a worse hrQoL for this patient group 13,23,24,27…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this large multicentre study from the Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart Disease International Study (APPROACH-IS), the authors compared physical functioning, mental health, and QOL as assessed by patient questionnaires in 3538 young adults (median age 32 years, interquartile range: 25 to 42) with a variety of congenital heart defects from 15 different countries. 8 For most measures, there were relatively small differences across the anatomic groups with the 72 patients who had cyanotic CHD or Eisenmenger syndrome, not surprisingly, consistently having the poorest scores across all measures. Other groups of concern from the data presented include Fontan patients and those with pulmonary atresia or congenitally-corrected TGA.…”
Section: What Should We Be Measuring?mentioning
confidence: 88%
“…Based on the occurrence of cardiac lesions in certain locations, CHD is clinically classified into >20 distinct subtypes, including ventricular septal defect (VSD), patent ductus arteriosus (PDA), transposition of the great arteries (TGA), double outlet of the right ventricle (DORV), tricuspid valve atresia (TVA), atrial septal defect (ASD), endocardial cushion defect, aortic stenosis, a right aortic arch, a single ventricle, tetralogy of Fallot, hypoplastic left heart and hypoplastic right heart (3)(4)(5)(6). Irrespective of minor CHD that may resolve spontaneously (3), major CHD may contribute to diminished health-associated quality of life (7)(8)(9), decreased exercise performance (10)(11)(12)(13)(14), delayed neurodevelopment and brain injury (15)(16)(17)(18), ischemic or hemorrhagic cerebral stroke (19)(20)(21), pulmonary arterial hypertension or Eisenmenger syndrome (22)(23)(24), viral pneumonia (25)(26)(27), infective endocarditis (28)(29)(30), acute myocardial infarction (31,32), chronic congestive heart failure (33)(34)(35), ventricular or supraventricular A novel KLF13 mutation underlying congenital patent ductus arteriosus and ventricular septal defect, as well as bicuspid aortic valve arrhythmia (36)(37)(38) and death (39)…”
Section: Introductionmentioning
confidence: 99%